1965
DOI: 10.1159/000129858
|View full text |Cite
|
Sign up to set email alerts
|

A Familial Centric Chromosome Fragment

Abstract: An extra centric chromosome fragment was found in the karyotype of an oligospermic male and his apparently normal mother. Both karyotypes were otherwise normal and the origin of the fragment could not be determined. The possible relationship, if any, between oligospermia and the chromosomal fragment cannot be established at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1967
1967
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The first occurs in an individual with a tiny centric chromosome fragment of unknown origin (Smith et al, 1965). These authors reported a sterile male with severe oligospermia in which arrest occurred at the spermatid stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first occurs in an individual with a tiny centric chromosome fragment of unknown origin (Smith et al, 1965). These authors reported a sterile male with severe oligospermia in which arrest occurred at the spermatid stage.…”
Section: Discussionmentioning
confidence: 99%
“…Does autosomal behavior also fall into a similar pattern to that depicted for sex chromo somes? In addition to the case of Smith et al (1965), there is the report of H ulten et al (1966) of a male carrying a tiny centric fragment of unknown origin. In H ulten's analysis, the tiny fragment appeared as a univalent in most cells at diakinesis and there were spermatids and a few abnormal sperm.…”
Section: Autosomal Examplesmentioning
confidence: 99%
“…Breakdown of spermatogenesis has been observed, for example, in individuals with an extra centric marker chromosome (Smith et al, 1965;H ulten et al, 1966;C handley, 1970), in individuals with an unbalanced form of a reciprocal autosome trans location (F redoa and R ayner, 1967), in a translocation mongol (H ulten and L indsten, 1970), and in an individual showing desynapsis of the bivalents at meiotic prophase (P earson et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…1976: Searle ct al, 1978Chandlcy, 1981: Joseph andThomas. 1982;Johannisson et al in a person with a reciprocal 14:21 translocation, personal communication): ring chro mosomes (Mcllree ct al, 1966: Moreau andTeyssicr, 1982): bisatellited microchromosomes (Smith et al 1965: Hulten et al 1966: Kjessler. 1966Chandley, 1970: a reduction of fertility is indicated in the review by Steinbach ct al.…”
Section: Conditions Conducive To Chromosomally-derived Male Sterilitymentioning
confidence: 99%